Effect of Laparoscopic Sleeve Gastrectomy on Serum Adipokine Levels - Cibičková, Ľ; Grega, M; Dohnal, R; Schovánek, J (Physiological research, 2023)
Bariatric procedures are considered to be the most effective treatment options for obesity. One of them is laparoscopic sleeve gastrectomy (LSG), which is nowadays very popular and widely used. LSG leads to weight loss and metabolic improvement and also changes adipokine levels, although it is just a restrictive operation. We describe changes in pro-inflammatory (leptin, resistin, visfatin and chemerin) and anti-inflammatory adipokines (adiponectin, omentin), with adiponectin and leptin being most studied. Their levels are markedly changed after LSG and this may partially explain the weight loss seen after LSG. Adipokines are closely connected to insulin resistance and chronic inflammation both being positively influenced after LSG. Leptin regulates amount of body fat, appetite, thermogenesis and metabolic rate and its levels are positively correlated with both weight and BMI changes after operation. Resistin influences insulin sensitivity, modulates body cholesterol trafficking and its changes after operation correlate with BMI, waist circumference, fat mass, LDL cholesterol and C-reactive protein. Chemerin, an important component of immune system, decreases after bariatric surgery and its levels correlate with BMI, triglyceride levels, and blood glucose. On the other hand, pro-inflammatory adipokine adiponectin, which influences fatty acid oxidation, browning of fat tissue and energy metabolism, is declining after LSG. This decline explains improvement of glucose status after bariatric surgery in patients with diabetes and is correlated with BMI loss, waist circumference and LDL cholesterol level. Effect of LSG goes beyond calory restriction and the changes of adipokines have a great impact on health status of the bariatric patients.
Keywords: leptin; Insulin Resistance; adiponektin; Cholesterol, LDL; inzulinová rezistence; resistin; Resistin; LDL-cholesterol; gastrektomie; Weight Loss; laparoskopie; Gastrectomy; lidé; Humans; Adiponectin; Adipokines; morbidní obezita; hmotnostní úbytek; Laparoscopy; Obesity, Morbid; adipokiny; Leptin